Cognitive-Behavioral Therapy in the Group on the Quality of Nurse’ Work Life - Mardhiah Mardhiah; Bustami Syam; Mahnum Lailan Nasution; Elvi Andriani Yusuf (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
There are many problems in the quality of nursing service found in hospitals, which is influenced by the quality of the work-life of nurses. An alternative way that can improve the quality of work-life of nurses is cognitive-behavioral therapy in group implementation. The study aimed to identify the effect of cognitive-behavioral therapy in the group on the quality of work-life of nurses in the inpatient room at the hospital. The study was quasi-experimental with a control group pre-posttest design. The sample of each group was thirty-two nurses selected by simple random sampling. Data were collected using questionnaires and analyzed by paired sample t-test and independent t-test. The result showed that there was a significant difference between the quality of work-life before and after intervention in both groups (p-value 0.027). Cognitive-behavioral therapy in the group has an impact on improving the quality of the work-life of nurses. Cognitive-behavioral therapy in the group can be applied in hospitals to improve the quality of the work-life of nurses  Abstrak: Ada banyak masalah dalam kualitas pelayanan keperawatan ditemukan di rumah sakit, yang mana berpengaruh dengan kualitas kehidupan kerja perawat. Salah satu cara alternative yang dapat meningkatkan kualitas kehidupan kerja pada perawa adalah implementasi cognitive-behavioral therapy in group. Tujuan penelitian untuk mengidentifikasi pengaruh cognitive-behavioral therapy in group terhadap kualitas kehidupan kerja parawat di ruang rawat inap rumah sakit. Penelitian ini adalah kuasi eksperiment dengan kelompok kontrol dengan rancangan sebelum dan sesudah. Sampel setiap kelompok adalah 32 perawat dipilih dengan simple random sampling. Data dikumpulkan dengan menggunakan kuesioner dan dianalisis menggunakan paired sample t-test and independent t-test. Hasil menunjukkan bahwa ada perbedaan yang significant diantara kualitas kehidupan kerja sebelum dan sesudah intervensi dalam kedua kelompok (p-value 0.027). Cognitive-behavioral therapy in group memiliki dampak terhadap peningkatan kualiats kehidupan kerja perawat. Cognitive-behavioral therapy in group dapat diterapkan di rumah sakit untuk meningktakna kualitas kehidupan kerja perawat.